Mutational Analysis of the Portuguese Cohort with Clinical Diagnosis of Familial Hypercholesterolemia - Medeiros, A.M. (2016)
Familial hypercholesterolemia (FH) is a common autosomal dominant disorder of lipid metabolism (1:500). FH patients present high levels of plasma cholesterol since birth, and if untreated, develop premature coronary heart disease (pCHD). To fulfil the World Health Organization recommendation (1998 report), the Portuguese FH Study was established in 1999. The aim of the Portuguese FH Study is to promote early identification and characterization of FH patients in order to decrease their cardiovascular risk by the implementation of correct/adequate and early counselling/treatment.